Boron-containing aptamers to ATP - Lato, S. M. (Nucleic acids research, 2002)
Boron neutron capture therapy (BNCT), an experimental treatment for certain cancers, destroys only cells near the boron; however, there is a need to develop highly specific delivery agents. As nucleic acid aptamers recognize specific molecular targets, we investigated the influence of boronated nucleotide analogs on RNA function and on the systematic evolution of ligands by exponential enrichment (SELEX) process. Substitution of guanosine 5'-(alpha-P-borano) triphosphate (bG) for GTP or uridine 5'-(alpha-P-borano) triphosphate (bU) for UTP in several known aptamers diminished or eliminated target recognition by those RNAs. Specifically, ATP-binding aptamers containing the zeta-fold, which appears in several selections for adenosine aptamers, became inactive upon bG substitution but were only moderately affected by bU substitution. Selections were carried out using the bG or bU analogs with C8-linked ATP agarose as the binding target. The selections with bU and normal NTP yielded some zeta-fold aptamers, while the bG selection yielded none of this type. Non-zeta aptamers from bU and bG populations tolerated the borano substitution and many required it. The borano nucleotide requirement is specific; bU could not be used in bG-dependent aptamers nor vice versa. The borano group plays an essential role, as yet undefined, in target recognition or RNA structure. We conclude that the bG and bU nucleotides are fully compatible with SELEX, and that these analogs could be used to make boronated aptamers as therapeutics for BNCT.